Reading and writing short - Vesterman, William (The McGraw-Hill Companies, 2005)
This argument text is a brief reader-rhetoric, offering a clear and concise introduction to argument and exceptionally accessible explanation of the Toulmin method along with a thematic collection of 68 short arguments.